Planning lessons and courses designing sequences of work for the language classroom - Woodward, Tessa (Cambridge, U.K. Cambridge University Press, 2001)
Designing sequences of work for language students.
Who are the students? -- How long is the lesson? -- What can go into a lesson? -- How do people learn and so how can we teach? -- What can we teach with? -- How can we vary the activities we do? -- Getting down to the preparation -- What are our freedoms and constraints?
Includes bibliographical references (p. 243-247) and index.
Keywords: Language and languages -- Study and teaching; Lesson planning